Carreadores lipídicos nanoestruturados para incorporação de complexos de cobre(ii) aplicáveis no estudo frente ao Mycobacterium tuberculosis - Sato, Mariana Rillo [UNESP] (2016)
Tuberculosis (TB) is known worldwide as the leading infectious disease of chronic evolution in which the abandonment of treatment before the recommended period tends to cause the development of more severe disease, such as the appearance of resistant strains. Copper interacts with biologically active ligands developing copper(II) complex with activities antimicrobial. Nanostructured lipid carriers (NLCs) have gained prominence in the pharmaceutical field, since they have the ability to compartmentalize efficiently lipophilic drugs and modify their properties and behavior in the biological environment. The aims of this study was to evaluate the potential of copper(II) complexes-loaded NLCs applicable in the study against Mycobacterium tuberculosis. Copper(II) complexes containing isoniazid binder were obtained and they were entitled C1, C2, and C3 where they have co-binders anionic chloride, cyanate and thiocyanate, respectively. NLCs were obtained by fusion-emulsification technique, formulations were obtained by Ultra turrax at 5000 rpm for 10 minutes followed by sonicator at 8% amplitude for 20 minutes to obtain stable NLCs, those were incorporated of 3.50% and 0.50% to surfactant poloxamer 407 and cetrimonium bromide, respectively, and 2.07%, 2.50% and 0.88% of polyoxyethylene stearate lipids, triglycerides of capric acid/caprylic and ethoxylated hydrogenated castor oil 40 OE (F32) or castor oil (F38), respectively. Copper(II) complexes were incorporated into NLCs (F32.OE.C1, F32.OE.C2, F32.OE.C3 and F38.OR.C1, F38.OR.C2, F38.OR.C3) and characterized by diameter (Dmn) , polydispersivity index (PDI) and zeta potential (ZP) for 1, 15, 30, 45 and 60 days, which revealed homogeneous dispersion and excellent physical stability over the same period; the atomic force microscopy confirmed that developed NLCs are spherical particles dispersions at nanometer scales; differential scanning calorimetry revealed that the constituents used in the formulations interacted in the systems and confirmed that copper(II) complexes were incorporated in the NLCs. The antimicrobial activity of the complexes against M. tuberculosis H37Rv was determined by the resazurin microdilution assay demonstrated potential anti-TB when complexes were incorporated into NLCs. Cytotoxicity assay in murine macrophage-like cells J774A.1 (ATCC TIB-67) e MRC-5 (ATCC-CCL-171) for 24 h and acute toxicity of the complex against Artemia salina L (Artemiidae) showed the formulations have toxicity in all tested concentrations; although published reports indicated the safety of the components used of the formulations, studies should be conducted in animal models to assess the acute toxicity. These results suggest that NLCs have potential application in the study against Mycobacterium tuberculosis.